Effect of restricted retail merchandising of discretionary food and beverages on population diet: a pragmatic randomised controlled trial. Issue 10 (October 2020) - Brimblecombe, Julie; McMahon, Emma; Ferguson, Megan; De Silva, Khia; Peeters, Anna; Miles, Edward; Wycherley, Thomas; Minaker, Leia; Greenacre, Luke; Gunther, Anthony; Chappell, Emma; Chatfield, Mark D; et al.
Summary: Background: The effectiveness of healthy food promotion on food and beverage sales in real-world food retail settings has been shown in randomised trials. The effectiveness of restrictions on the promotion of unhealthy food is, however, less clear. We aimed to assess the effect of restricted unhealthy food promotion, specifically those items contributing most to free sugar sales, on food and beverage sales. Methods: In this community-level pragmatic, partially randomised, parallel group trial, stores were randomly assigned by a statistician using a single sequence of random assignments to the intervention group, in which a co-designed strategy restricted merchandising of unhealthy food, or to a control group of usual retail practice. The trial was done in partnership with an organisation operating 25 stores in remote Australia. The primary analysis was based on difference in weekly sales with the strategy compared with no strategy in free sugar from all foods and beverages (g/total MJ; primary outcome), targeted food or beverages (weight and free sugars; g/total MJ), and gross profit (AU$) using mixed models. This trial is registered with the Australian New Zealand Clinical Trials Registry, ACTRN12618001588280. Findings: Between June 13 and Aug 15, 2018, 20 stores were recruited; ten stores were randomly assigned to the intervention group and ten stores to the control group. The trial was done between Sept 2 and Dec 2, 2018. The Healthy Stores 2020 strategy resulted in a reduction in sales of free sugar of 2·8% (95% CI –4·9 to –0·7). Targeted beverages were reduced by 8·4% (–12·3 to –4·3) and associated free sugar by 6·8% (–10·9 to –2·6), sugar-sweetened soft drinks by 13·2% (–18·5 to –7·6), and associated free sugar by 13·4% (–18·7 to –7·7). Reductions in sales of free sugar from confectionery of 7·5% (–14·3 to –0·2) and in weight sold (–4·6%, –11·1 to 2·3) resulted; however, the reduction in weight was not statistically significant. No differences in sales of table sugar and sweet biscuits were observed. Gross profit was not impacted adversely; a small increase resulted (5·3%, 0·3 to 10·5). Interpretation: Restricted merchandising of unhealthy foods and beverages, while allowing for complementary merchandising of healthier foods and beverages in a real-world store setting and co-designed with retailers, can achieve both public health and business relevant gains. Funding: Australian National Health and Medical Research Council.